Mechanism of Olibanum and Myrrha for the Acute Soft Tissue Injury Based on Network Pharmacology - Tan, Miao; Cheng, Yan (Chinese medicine and natural products, 2022)
Objective The objective of this study was to screen the therapeutic target of olibanum and myrrha on acute soft tissue injury (ASTI) by network pharmacology and to clarify their mechanisms.Methods The main chemical constituents and the targets of olibanum and myrrha were obtained by using traditional Chinese medicine systems pharmacology database and analysis platform database. The disease targets of ASTI were searched by GeneCards. The intersection targets of herbs and diseases were selected for protein interaction analysis, protein–protein interaction network was constructed, and potential protein functional modules in the network were explored. A compound–target–disease network was constructed using Cytoscape3.8.2 software. The targets were analyzed by gene ontology analysis and Kyoto Encyclopedia of Genes and Genomes enrichment analysis based on the Metascape database.Results The core active components of olibanum and myrrha were quercetin, β-sitosterol, and stigmasterol. The core targets were PGR, NCOA2, PTGS2, PRKCA, and NR3C2. Pathways in cancer, AGE-RAGE signaling pathway in diabetic complications might play a potential role in olibanum and myrrha in the treatment of ASTI.Conclusion Olibanum and myrrha have the characteristics of multiple components, multiple targets, and overall regulation in the treatment of ASTI.
Keywords: olibanum and myrrha; acute soft tissue injury; network pharmacology